Трям! Здравствуйте! - Козлов Сергей Григорьевич (Наши любимые мультфильмы, 2014)
Экземпляры: (20220121) / Инвентарный номер: 4311 / Цена: / Сис.шифр: 84(2Рос) / Авт.знак: К 59 / ГРНТИ: 17.82.93 / ББК: 84(2Рос)6